Risk Adjustment for Congenital Heart Surgery Score as a Risk Factor for Candidemia in Children Undergoing Congenital Heart Defect Surgery. Issue 11 (November 2016) - de Araujo Motta, Fabio; Dalla-Costa, Libera Maria; Dominguez Muro, Marisol; Lenzi, Andrea; Picharski, Gledson Luiz; Burger, Marion
Abstract : Background: Candida species are the primary cause of invasive fungal infection in hospitalized children. There are few data on risk factors for postoperative candidemia in pediatric patients with congenital heart defects. This study aimed to identify risk factors for candidemia in patients with congenital heart defects who underwent cardiac surgery. Methods: This was a case-control study conducted in patients admitted to a pediatric cardiology intensive care unit from January 2006 to December 2013. Candidemia cases were matched with control patients without candidemia. Multivariate analyses were conducted to determine predictive probabilities for the incidence of candidemia at a risk higher than 10%. Results: Thirty patients diagnosed with candidemia (incidence: 0.7 cases/1000 patient days) were matched with 75 controls. Risk factors independently associated with candidemia included Risk Adjustment for Congenital Heart Surgery (RACHS-1) category ≥3 [odds ratio (OR) = 3.165, 95% confidence interval: 1.377–8.467], use of acid suppression therapy (OR = 1.9, 95% confidence interval: 0.949–3.979) and thrombocytopenia (OR = 2.2, 95% confidence interval: 1.2–4.2). Predictive probabilities ranged from 11% (only in RACHS-1 category ≥3) to 58% (combined RACHS-1 ≥3, thrombocytopenia and acid suppression therapy use). The case fatality rate within 30 days after candidemia was 50%. Conclusion: This is the first report using the RACHS-1 category as a risk factor for invasive candidiasis in patients with congenital heart defects in the pediatric intensive care unit. Further studies must be conducted to validate the risk factors for candidemia in this pediatric population.